Penerapan Konsep Ash-Shiddiq Pedagang Temporer pada Wisata Mappogau Sihanua di Kabupaten Sinjai - Darnayanti Darnayanti; Irwan Misbach; Wahid Haddade (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2022)
The dependency between a human with another human cannot be denied anymore so that it's needed a collaboration to fulfil their life based on Islam recommendation. A good Muslim is who does work that not conflict with Islamic law. Since the birth of Islam, trading has been known as a lines of fulfilling the necessities of life which is halal and recommended. The same thing happened at Tompobulu village, Bulupoddo, Sinjai where the temporary traders appeared at the certain time in a traditional party held " Mappogau Sihaua". Through this activity the trader should apply the concept of trading that has been regulated by Islam based on values and ethics that come from the basic values of religion, especially upholding the value of honesty (Ash- Shidiq) and justice, instead of taking advantages of this situation by getting the greatest profit without paying attention to the good values of trading. The temporary trader should apply Ash-Shidiq according to Islamic business ethics so that their business gets the blessing of Allah Swt. The prophet has laid down the principle of Ash- Shidiq as the basic for the implementation of justice and honesty in trading. With honesty, it is hoped that the trade of a Muslim will progress and develop.